2018
DOI: 10.26896/1028-6861-2018-84-7-42-46
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of corrosive atmospheres for evaluation of the efficiency of volatile inhibitors

Abstract: A method of modeling aggressive atmospheres used for different tests in corrosive environments close as possible to actual full-scale conditions is proposed. The method provides simulation of air atmospheres containing gaseous corrosion stimulants (CS) as microcomponents of air. The content of SCs in such atmospheres (both separately and together) can be set and maintained at an unchanged level within a wide range for as long as desired. The method is based on Henry’s equation characterizing concentration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Several studies reported in the past decade on the corrosion inhibition of different types of steel in a CO 2 /H 2 S coexisting environment, [66–67,71a‐c,72,76,115,131d,140] as presented in Table 2. The solutions employed in these studies, consisting of either NaCl solutions [71–72,76,115,131d,140a] or brine and simulated oilfield waters, [66–67,140b,c] were usually saturated with both CO 2 and H 2 S. In a few of these studies, the authors also reported on the influence of either the pressure/concentration of CO 2 and H 2 S or their ratio on the corrosion inhibition of the respective CIs [66,72,76,115,140a] . In addition, Qiu et al [140b] .…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported in the past decade on the corrosion inhibition of different types of steel in a CO 2 /H 2 S coexisting environment, [66–67,71a‐c,72,76,115,131d,140] as presented in Table 2. The solutions employed in these studies, consisting of either NaCl solutions [71–72,76,115,131d,140a] or brine and simulated oilfield waters, [66–67,140b,c] were usually saturated with both CO 2 and H 2 S. In a few of these studies, the authors also reported on the influence of either the pressure/concentration of CO 2 and H 2 S or their ratio on the corrosion inhibition of the respective CIs [66,72,76,115,140a] . In addition, Qiu et al [140b] .…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
“…Table 2 shows that the compounds used as CIs in a CO 2 /H 2 S coexisting environment were mostly imidazoline derivatives, [66,71b,72,115,140a,141] quaternary ammonium salts, [66,67b,71b,72,140b] and Gemini surfactants [67a,b] . A few CIs employed in this environment were obtained as a combination of different organic compounds, including azole compounds, polyamines, and organic acids [76] . Moreover, Rivera‐Grau et al [131d] .…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in the hydrolysis of + 4 NH and S 2ions to form NH 4 OH and H 2 S, which are stable in the surface phase film, as noted above. To compare the results obtained by electrochemical and weight tests, the latter were carried out in sealed desiccators with a volume of 7 L, where the specified concentration of CSs was created in the gas phase according to the method proposed by the authors of the article [7]. The value of 100% relative humidity in the desiccators was achieved by the presence in them of an additional small capacity with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Введение. Для противокоррозионной защиты сельскохозяйственной техники традиционно используют консервационные материалы на масляной основе, как одни из самых доступных [1][2][3][4][5][6][7][8] и водно-восковые составы [9][10][11]. В ФГБНУ ВНИИТиН в последние годы ведутся разработки по исследованию возможности использования летучих ингибиторов коррозии (ЛИК) для этих целей [12][13][14][15][16][17].…”
unclassified